The phenomenon of racism and the concept of race: a transdisciplinary research - Novikova, Olga V. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
In recent decades, with development of scientific and philosophical knowledge, the transdisciplinary approach has become relevant, as it aims at comprehensive study of complex natural and social phenomena. Racism belongs among such phenomena, and it it is usually studied in sociology and historical science. The article presents a transdisciplinary study of racism, involving a complex appeal to philosophy, history, sociology, and other disciplines. Special attention is paid to the philosophical conceptualisation of racism and the relationship of racism with the category of race. The article follows the evolution of the concept of race in philosophy, science and social and political practices from its origins to the 20th and 21st centuries, when this concept is declared to be artificially constructed and is gradually ousted from philosophical and scientific discourse. Bioanthropologists criticise the concept of race as inaccurate, while intellectuals see racial classifications as a sign of racism. The difficulty of the conceptualisation is associated not only with the variability of the concept of race but also with the change in its historical types, from traditional to contemporary ones. Traditional (classical, biological) racism is based on the use of the category of race and the idea of insurmountable biological differences between representatives of different races. The article concludes that present-day racism exists in two forms: class (institutional) racism and cultural (differential or «subtle») racism. Class racism is associated with social and political practices of implicit segregation in employment and, accordingly, with unequal distribution of income. Cultural racism shifts the focus from biology to culture and emphasises the insurmountability of cultural differences.
Keywords: social philosophy; philosophical anthropology; racial taxonomy; biological racism; class racism; cultural racism